Fobia sosial Tokoh Satou Tatsuhiro dalam Manga NHK ni Youkoso! Karya Takimoto Tatsuhiko - Valentina Arwanto, Theresia; Budiana, I Made (Humanis, 2018)
The title of this research is “ Social phobia of the character Satou Tatsuhiro in Takimoto Tatsuhiko’s Manga NHK ni Youkoso!”. The purpose of this research is to know the symptoms and causes of social phobia, and also the efforts done by character Satou Tatsuhiro to overcome his social phobia of Satou Tatsuhiro. The research methods used are descriptive analysis and formal informal methods. There are four theoris used in these research, such as the theory of  literature psychology by Ratna, theory of social phobia by Philips, m. d. et all, Nevid, a. Rathus and Greene, theory of  cognitive behavior by Butler and semiotics theory by Marcel Danesi. Based on the results in this research, there are eight social phobia, such as, 1) The fear or anxiety of one or more social situations; 2) Fear of getting bad judgment; 3) Fear or anxiety is excessive; 4) Tends to avoid social situations; 5) Fear or anxiety is not in accordance with the impact; 6) Fear or anxiety lasts for six months or more; 7) The fear or anxiety have a negative impact on daily life; 8) are not caused by the physiological effects of a substance. Character Satou Tatsuhiro meets all the symptoms of social phobia. These are two factors causing character Satou Tatsuhiro to have social phobia, that are; 1) cognitive factors that taste sensitive to a threat of excessive and irrational thoughts and 2) socio-cultural factors, namely the environment of school, home and parenting. The effort done by character Satou Tatsuhiro to overcome his  social phobia are 1) Changing the mindset; 2) doing something different; 3) reduces the self consciousness; 4) Build confidence.